High-Resolution CT Thorax and Serum IL-6 Levels in Patients with Interstitial Lung Disease - Beenish Javaid, Naeem Ahmad Khan, Fatima Iqbal, Nazish Khalid, Anam Shafique, Noman Johnson, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Interstitial lung diseases (ILDs) represent a diverse group of chronic lung disorderscharacterized by inflammation, fibrosis, and impaired gas exchange. High-resolution computedtomography (HRCT) is considered the imaging gold standard for diagnosis andcharacterizationof ILDs. Meanwhile, interleukin-6 (IL-6), a pro-inflammatory cytokine, has emerged as a potentialbiomarker.